A taxonomic study of Trechnites Thomson (Hymenoptera: Encyrtidae) from China - Zou, Bo-Yu; Zu, Guo-Hao; Zhang, Yan-Zhou (Zootaxa, 2026)
Seven species of Trechnites Thomson from China are taxonomically studied. Three species are newly described: T. cacopsyllae Zou, Zu & Zhang, sp. nov., T. monticola Zou, Zu & Zhang, sp. nov. and T. yunnanensis Zou, Zu & Zhang, sp. nov. An additional species, T. concinnus Kazmi and Hayat, is newly reported from China. Diagnoses or descriptions, microphotos of key characters, as well as the known distribution and hosts of each species are provided. A dichotomous key is also given to facilitate the identification of species.